PENGARUH PROMOSI TERHADAP MINAT BELI KONSUMEN DI PT ZPAY KOMUNIKA - Kasih Karunia Wati Zega; Otanius Laia; Idarni Harefa; Tiarni Duha (Jurnal Publikasi Manajemen Informatika, 2026)
Promotion is an activity designed to influence consumers so they become familiar with the products offered by the company, thus becoming interested and purchasing them. Purchase intention is a consumer behavior that underlies a purchasing decision. This study aims to determine whether there is an influence of promotion on consumer purchase intention at PT ZPAY Komunika and to determine the extent of the influence of promotion on consumer purchase intention at PT ZPAY Komunika. The research method used was quantitative research with 30 respondents. The results of the data analysis showed that the calculated t-value for the variable 6.099 was >2.054, thus concluding that Ha was accepted and that promotion had an effect on the variable consumer purchase intention. Based on the Adjusted R Square value of 0.672, this indicates that the promotion variable can influence consumer purchase intention by 55.5%. The remainder is influenced by other variables not discussed in this study.